Three new species of Pselaphogenius Reitter (Coleoptera: Staphylinidae: Pselaphinae) from Nanling Mountain Area, China - Zhang, Yong-Qin; Yin, Zi-Wei (Zootaxa, 2024)
Prior to this study, no species of the tribe Pselaphini (Pselaphinae: Pselaphitae) have been known from southern China. Here we report the discovery of the genus Pselaphogenius Reitter, and describe three new representatives from Nanling Mountain Area, namely, P. buccalis sp. nov., P. huapingensis sp. nov., and P. magnus sp. nov. All taxa are diagnosed and compared to similar congeners; and images of the habitus and major diagnostic characters are provided. A map showing the distribution of the Chinese species of Pselaphogenius is given.